AN ANALYSIS OF CODE-SWITCHING IN GRACE TAHIR AND MERRY RIANA'S UTTERANCES ON MERRY RIANA'S PODCAST - Lusy Agnesia Sitanggang; Lisbeth Juliana Sidauruk, Enmia Virnanda Munte, Christine L.Tobing, Evelyn Zebua, Meisuri. S. A., Gi (Adisam Publisher, 2025)
The majority of Indonesian public figures speak both Indonesian and English, which contributes to the problem of code-switching.In order to better understand the phenomenon of code switching, this study looked at the various forms and justifications for its use by Merry Riana and Grace Tahir on their November 19, 2021, YouTube channel,